BODY MASS INDEX, BODY FAT PERCENTAGE, FLEXIBILITY, PHYSICAL ACTIVITY LEVEL AND SATISFACTION IN PHYSICAL EDUCATION CLASSES OF 7 AND 10 YEARS OLD CHILDREN ON PRIVATE AND PUBLIC SCHOOLS AT MUZAMBINHO-MG (Fiep Bulletin - online, 2012)
Nowadays, the world level of physical activity among young people is decreasing in proportion to the increase in the percentage of fat and worsening in the performance of motor activities. In order to investigate this, the present study aims to compare the body mass index, body fat percentage, flexibility, physical activity level and satisfaction level in physical education classes for 7 and 10 years old children in public and private schools at Muzambinho-MG. The sample comprised 115 children living in the district of Muzambinho-MG in both genres in 2011 enrolled in private schools (n = 37) and public schools (n = 78) aged as 7 and 10 years old. It was determined the body mass index (BMI), percentage fat (% BF) by skinfold triceps and calf (FERNANDES FILHO, 2003). The measure of the flexibility levels was performed using the Sit and Reach protocol (WELLS; DILLON, 1952). To determine the level of physical activity and satisfaction in physical education classes was applied questionnaire "Typical Day Physical Activity and Food - DAFA" -modified (BARROS; NAHAS, 2003). At the end of this study can be seen that although there are significant differences in levels of physical activity groups, children in public schools were more satisfied with the physical education classes and children from the private schools are presented above BMI, % BF and flexibility.
Keywords: physical education classes; physical activity; children.